Food insecurity associated with self-reported mental health outcomes in Peruvian households during the COVID-19 pandemic - Anampa-Canales, Maria M.; Huancahuire-Vega, Salomón; Newball-Noriega, Edda E.; Morales-García, Wilter C.; Galvez, Cesar Augusto (Frontiers in Nutrition, 2022)
Background The global pandemic of COVID-19 and the social distancing efforts implemented worldwide to limit its spread have disrupted the economy, increased food insecurity, and mental health problems. Objectives The aim of this study was to determine the association between food insecurity and mental health outcomes (stress, depression, and anxiety) in Peruvian households during the COVID-19 pandemic. Materials and methods A cross-sectional investigation was conducted with 525 participants of both sexes (68% women), over 18 years of age and from the three geographic regions of Peru: Coast (54.9%), Highlands (28.4%), and Jungle (16.8%). The data were collected during the year 2021, between July 6 and September 22 through a self-administered online survey designed to assess socio-demographic, socioeconomic, food insecurity, and mental health outcomes (depression, anxiety, and stress). Results The majority of households (71.4%) experienced some degree of food insecurity. Mild food insecurity was the most frequent, affecting 49.1%, followed by moderate 15.4%, and severe 6.9%. Regarding mental health outcomes, 24.8% manifested depression, 26.7% anxiety, and 15.3% stress. With respect to the association between the level of food insecurity and anxiety, this was highly significant (p < 0.01). Households with mild, moderate and severe food insecurity are 2.04, 4.5, and 10.44 times, respectively, more likely to have moderate-severe anxiety. On the other hand, the mild food insecurity was not associated with moderate-severe depression. In contrast, households with moderate and severe food insecurity are 2.8 and 5.7 times, respectively, more likely to have moderate-severe depression. Finally, households with moderate food insecurity are 5.9 times more likely to have moderate-severe stress, and households with severe food insecurity are 8.5 times more likely to have moderate-severe stress, both having a highly significant association (p < 0.01). Conclusion In conclusion, during the second wave of the COVID-19 pandemic in Peru, household food insecurity was independently associated with worse mental health outcomes. Monitoring of both food insecurity and mental health will be important as the COVID-19 pandemic continues.